HIDDEN ACTION IN THE CASE OF TAX DISPUTES IN INDONESIA - Inayati Nuraini Dwiputri (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This research aimed to conduct a study for tax dispute cases in Indonesia, which refers to the behavior of the Supreme Court’s verdict and indication of hidden action done by taxpayer in an effort to win tax disputes and to analyze the taxation regulations especially on the case of tax disputes. The research data are Supreme Court’s verdicts 2004-2010 on the tax disputes cases.This research uses descriptive and logistic regression analysis. The result shows the Supreme Court’s verdict has different way of treating tax year, the length of processingdisputes, and the difference of calculation between taxpayers and tax apparatus. The analysis indicates that hidden action is done by taxpayers in an effort winning the tax disputes. The higher difference of calculation, the higher probability for taxpayers to win the tax disputes. The longer processing time of tax disputes on the level of Supreme Court the higher probability for taxpayers winning the disputes. This indicates the public functionary’s involvement in hidden action by taxpayers. The hidden action done can be in the form of corruption, collusion, and bribery. The analysis of taxation regulation indicates that Indonesian taxation regulations have not been implemented well anddeviation is still found.From this research result and the reference to the previous researches, it is identified that the Indonesian government is required to do things such as: 1) promoting the qualityof tax apparatus either intellectually or through moral behavior; 2) promoting the obedience of taxpayer by promoting the benefits of paying tax especially for taxpayers; 3) inviting citizens/societies and social institution to fight against corruption; 4) promoting the obedience to the taxation regulation for taxpayers and tax apparatus; 5) designing a better taxation institution; 6) shortening the time for the process of disputes.Keywords: hidden action, corruption, the Supreme Court’s verdict, taxpayers.